Increased body fat mass reduces the association between fructosamine and glycated hemoglobin in obese type 2 diabetes patients. Issue 4 (17th September 2020) - Vergès, Bruno; Rouland, Alexia; Baillot‐Rudoni, Sabine; Brindisi, Marie‐Claude; Duvillard, Laurence; Simoneau, Isabelle; Legris, Pauline; Petit, Jean‐Michel; Bouillet, Benjamin
Abstract: Obesity is increasing in patients with type 2 diabetes. A possible reduced association between fructosamine and glycated hemoglobin (HbA1c) in obese individuals has been previously discussed, but this has never been specifically evaluated in type 2 diabetes, and the potential influence of body fat mass and fat distribution has never been studied. We studied 112 type 2 diabetes patients with assessment of fat mass, liver fat and fat distribution. Patients with body mass index (BMI) above the median (34.9 kg/m 2 ), versus BMI below the median, had a correlation coefficient between fructosamine and HbA1c significantly reduced ( r = 0.358 vs r = 0.765). In the whole population, fructosamine was correlated negatively with BMI and fat mass. In multivariate analysis, fructosamine was associated with HbA1c (positively) and fat mass (negatively), but not with BMI, liver fat or fat distribution. The association between fructosamine and HbA1c is significantly reduced in the most obese type 2 diabetes patients, and this is mostly driven by increased fat mass. Abstract : The association between fructosamine and glycated hemoglobin is significantly reduced in the most obese type 2 diabetes patients, and this is mostly driven by increased fat mass.